Hubungan Kepemimpinan Transformasional Kepala Sekolah, Kreativitas Guru dan Kepuasan Kerja Guru terhadap Kinerja Guru Sekolah Menengah Pertama Se-Kecamatan Tanjung Kabupaten Tabalong - Iseu Widiartina; Ahmad Suriansyah; Aslamiah Aslamiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the relationship between principals' transformational leadership, teacher work creativity, and teacher job satisfaction and performance in junior high schools in Tanjung District, Tabalong Regency. This research approach is quantitative. The population of this study consisted of all junior high school teachers in Tanjung District, with a total of 148 teachers, and the sample size was 110 people. The data collection technique uses a questionnaire distributed widely to the sample. Analysis of research results using descriptive statistics, simple regression, and multiple regression using SPSS Window Version 25. The research results show that there is a relationship between the transformational leadership of school principals on teacher performance, work creativity on teacher performance, job satisfaction on teacher performance, transformational leadership principals on work creativity, principals' transformational leadership on job satisfaction, principals' transformational leadership on teacher performance through job creativity, transformational leadership on teacher performance through job satisfaction. In conclusion, there is a relationship between the transformational leadership of school principals, teacher work creativity, and teacher job satisfaction and teacher performance in junior high schools in Tanjung District, Tabalong Regency. Keywords: Job Satisfaction, Transformational Leadership, Work Creativity, Performance